Manajemen Organisasi Santri Dalam Mewujudkan Pesantren yang Lebih Baik - Maryam Huda (Jurusan Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2018)
The research aims to identify the management process implemented by the Al-Ihsan Boarding School’s Student Organization (OSPAI) in impoving the quaity of the school. The study used descriptive method that explain dan describ the whole management proces carried out by OSPAI. The data collected through observation, interview, and document’s study on the availabe data from the organization committee. The research finds that the organization implements a number of management processes that incllude planning, organizing, actuating, controlling, and evaluating. The planning process includes the implementation of regulation, recruitment of committees candidates, organization’s program formulation, budgeting. Actuating process includes program implementation. Controlling process carried out through a number of regular meeting. Evaluation process, meanwhile, mainly consists of whole program report delivered by the committee in the student general meeting.